Design like Apple : seven principles for creating insanely great products, services, and experiences - Edson, John, 1966-; Beck, Ernest, ....- (Hoboken, N.J. : Wiley, 2012)
Implement the same principles that shaped Apple's approach to design Apple sees design as a tool for creating beautiful experiences that convey a point of view down to the smallest detail--îfrom the tactile feedback of keyboard to the out-of-the-box experience of an iPhone package. And all of these capabilities are founded in a deep and rich embrace of what it means to be a designer.
Includes bibliographical references and index.
Keywords: Apple Computer, Inc; Product design